Novel Genes Affecting Urease Activity in Actinobacillus pleuropneumoniae - Bossé, Janine T. (American Society for Microbiology, 2001)
Characterization of a series of urease-negative transposon mutations of Actinobacillus pleuropneumoniae revealed that many of the mutants had insertions 2 to 4 kbp upstream of the urease gene cluster. A 5-kbp upstream region of DNA was sequenced and found to contain six open reading frames (ORFs) transcribed in the same orientation as the urease genes. As well, a partial ORF, apuR, 202 bp upstream of these six ORFs, is transcribed in the opposite orientation. The predicted product of this partial ORF shows homology with many members of the LysR family of transcriptional regulators. Five of the ORFs (cbiKLMQO) appear to form an operon encoding a putative nickel and cobalt periplasmic permease system. The cbiM and cbiQ genes encode proteins that have sequence similarity with known cobalt transport membrane proteins, and the cbiO gene encodes a cobalt transport ATP-binding protein homologue. The product of the cbiK gene is predicted to be the periplasmic-binding-protein component of the system, though it does not show any sequence similarity with CbiN, the cobalt-binding periplasmic protein. Escherichia coli clones containing this putative transport operon together with the urease genes of A. pleuropneumoniae were urease positive when grown in unsupplemented Luria-Bertani broth, whereas a clone containing only the minimal urease gene cluster required the addition of high concentrations of NiCl(2) for full urease activity. This result supports the hypothesis that nickel is a substrate for this permease system. The sixth ORF, utp, appears to encode an integral membrane protein which has significant sequence identity with mammalian urea transport proteins, though its function in A. pleuropneumoniae remains to be determined.